Diffuse Pericoronary Soft-Tissue Cuffing on Coronary Computed Tomography Angiography in a Patient with Unstable Angina: Possible IgG4-Related Coronary Periarteritis - Shuo Liang; Dan Li; Hong Zhang (Diagnostics, 2026)
A 66-year-old man with hypertension, type 2 diabetes mellitus, and a 50-year smoking history was presented with acute chest pain clinically consistent with unstable angina. Coronary computed tomography angiography (CCTA) showed multivessel atherosclerosis and, more strikingly, diffuse sheath-like pericoronary soft-tissue cuffing around the major epicardial arteries—an appearance reported as the “mistletoe sign” and compatible with immunoglobulin G4 (IgG4)-related coronary periarteritis. CT-derived fractional flow reserve (CT-FFR) measured 0.75 in the left anterior descending artery, 0.68 in the left circumflex artery, and 0.94 in the right coronary artery. Invasive angiography identified a 90% proximal left circumflex stenosis as the flow-limiting lesion; drug-eluting stent implantation restored Thrombolysis in Myocardial Infarction (TIMI) grade 3 flow. Serum IgG4 (145 mg/dL) was only marginally above the diagnostic threshold, and troponin was unavailable, so the diagnosis remained clinical. Without histopathology, the findings support possible rather than definite IgG4-related disease, and the contribution of the pericoronary process to the stenosis could not be established. The patient remained stable on conventional medical therapy. CCTA, CT-FFR, and angiography answer complementary questions; diffuse pericoronary change warrants serologic and systemic evaluation for inflammatory coronary involvement, with cautious etiologic attribution.